Information ethics and pluralism in the age of globalization (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
Speaking about information ethics, we must take into account the enormous influence of the Internet on the psychology of people to determine information culture in order to protect the individual from the negative influences of the global Network. Connections and relationships between people began to be measured by the degree of familiarization with technological objects and turned into an ontological object with new spatiotemporal properties. The impact of information and communication technologies on society gives rise to new contradictions and restrictions, despite the fact that in the era of “techno-info”, man and information ethics are considered as the unity of achieving social balance. On the other hand, we cannot ignore the ethical aspect here.
Keywords: Information ethics, homo-informaticus, virtual reality, Internet communications, existential question of the future